COACHING PROGRAM EVALUATION CORDOVA FUTSAL CLUB - Muhamad Ade Syahputra; Moch Asmawi; Iman Sulaiman (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to evaluate the coaching program at the Cordova futsal club, which is one of the sports associations that fosters and develops futsal in South Tangerang in particular and in Indonesia in general. In this evaluation, the research uses a survey method using the CIPP model, namely, Context, Input, Process, Product. The results of this study concluded that: the context stage, the Cordova futsal club coaching program was considered very good, the implementation was carried out according to the Vision and Mission. Then the Goals and Strategic Plans are the guidelines and references in the implementation of the coaching program. The input stage, which involves the performance of associations, coaching and training programs, athletes, availability of trainers, infrastructure and sources of funds is rated Very Good, obtained 82.5%. The process stages include the implementation of the coaching program and the effectiveness of the program implementation is considered good, with an average rating of 80.5%. The last stage, namely the product stage that is evaluated, is the achievement of targets in regional, provincial and national events.